Does ISO 26000 Corporate Social Responsibility Influence Company Performance? - Prayuda, Rafie Zaidan; Praditya, Rayyan Aqila (Journal of Industrial Engineering & Management Research, 2020)
The purpose of this study is to analyze the influence of implementation of ISO 26000 Corporate Social Responsibility (CSR) on Business performance of automotive industries located in West Java. Research respondents were staff and management of 5 automotive companies consist of 212 people and the method of data collection use electronic questionnaires by snowball sampling to all respondents. This study use a quantative method and analysis tools in this study is SEM (Structural Equation Model) with the LISREL program version 8.70. The results showed that the ISO 26000 Corporate Social Responsibility (CSR) had a posutive and significant effect on business performance This research novelty is essential as it outlines a strategic model that could be adapted and adopted by other industries in Indonesia or in other regions in improving their business performance by implement ISO 26000 Corporate Social Responsibility (CSR) in their companies.